Comportamento tribocorrosivo em liga austenítica AISI 316L modificada superficialmente a plasma em atmosfera livre de gás hidrogênio - Mario Jose Bueno de Souza Freitas (2019)
In order to make feasible the use of austenitic stainless steels in applications where high sliding wear and corrosion resistance are required, this work aimed at the study of the surface modification of the AISI 316L austenitic stainless steel using an innovative process of sequential hydrogen-free plasma treatment and atmosphere containing high concentration of N2 (70%) in addition to Ar (30%). Plasma nitriding was performed at 460°C for 5 hours and plasma cementation at 475°C for 4 hours. It was not observed in the current literature record the use of this process with the characteristics and parameters selected. Two sample systems were produced: 1-TPC+TPN = plasma-carburized samples followed by plasma nitriding; 2- (Cr-N)TPC+TPN = plasma-carburized samples followed by plasma nitriding with subsequent deposition of Cr-N coating processed by PAPVD. It was found that the treatment resulted in the formation of a double layer of expanded austenite, the first one rich in nitrogen followed by a carbon-rich layer. In the (Cr-N)TPC+TPN system was the production of a thick coating (7μm) deposited on the plasma-modified AISI 316L () austenitic steel with the presence on the surface of the layers of austenite expanded by nitrogen (N) and carbon (C). As a result of the double-layer structure, added to the coating, a superior surface hardening was found in the (Cr-N)TPC+TPN system, followed by the TPC+TPN system, compared to the untreated AISI 316L. Joint analyzes with SEM and instrumented hardness in the cross-section of the samples, the formation of a layer of austenite with a high content of nitrogen solubility, much thicker than systems already studied and registered in the literature, was verified. In both systems, a high hardness-depth was produced ((Cr-N)TPC+TPN ~ 38 μm; TPC+TPN ~ 33 μm). As a result of this hardening, an excellent response to sliding wear was obtained, verified by the significant decrease in the measured worn volume and in wear track depth. Between the treated systems, the lowest worn volume was observed in the (Cr-N)TPC+TPN system (~ 1000X lower than AISI 316L), followed by the TPC+TPN system (~ 10X lower than AISI 316L). The XRD analyzes shown that the deposited coating was composed of a complex mixture of phases (CrN, Cr2N, and Cr), as already reported in the literature. On the other hand, the absence of precipitates was confirmed in the TPC+TPN diffractogram. This outstanding result is directly linked to the chosen plasma treatment parameters. The observation of high nitrogen (N) austenite free of iron/chromium nitrides played a crucial role in the improvement of the corrosion/tribocorrosion in this plasma treatment system compared to the 316L austenitic steel. The sequential plasma treatment used provided the increase in Ecorr, Epit, and excellent repassivation power for AISI 316L, even in the presence of sliding wear. The same behavior was not observed in steel without plasma treatment. Finally, it was found that by sequential plasma treatments, it was possible to achieve a drastic reduction in the wear volume after tribocorrosion tests compared to untreated steel. This high resistance to sliding wear made it impossible to measure the volume of material removed from the (Cr-N)TPC+TPN system since it is below the limit of the technique (3D profilometry). It is demonstrating, once again, excellent material performance after plasma treatment